Psychological Consequences of Sports Injuries in Adolescents - Faryna-Cichoń, Aleksandra; Psiuk, Arkadiusz; Szymocha, Joanna; Wojas, Aleksandra; Tsukerman, Jarosław; Smędowski, Igor (Quality in Sport, 2026)
Background: Sports injuries carry not only physical consequences but a broad spectrum of psychological sequelae that may permanently affect adolescent functioning. Systematic psychological support for injured adolescent athletes remains markedly underimplemented in clinical practice and sport governance. Aim: To review current evidence on the psychological consequences of sports injuries in adolescents, with emphasis on mood disorders, PTSD symptoms, athletic identity disruption, kinesiophobia, and psychological readiness to return to sport. Material and methods: Narrative review of literature from 2017 to 2026, encompassing systematic reviews, meta-analyses, prospective cohort studies, and qualitative investigations on psychological sequelae of sports injuries in adolescents aged 10–19 years. Results: Sports injuries are associated with significantly elevated risk of depression, anxiety, and PTSD. A meta-analysis of 84 studies (n = 221,095) confirmed a bidirectional relationship between mental health and injury risk (OR = 1.54; 95% CI 1.13–2.10). Post-injury depression rates were 23% in females vs. 8.8% in males. ACL-RSI scores increased from 55 to 71 between 6 and 12 months post-reconstruction, exceeding the minimal important change threshold (15.8 vs. 13.4). High kinesiophobia (TSK-11 >19) at return to sport was associated with a 13-fold increased risk of repeat ACL injury. PTSD avoidance symptoms were present in >87% of young athletes after ACL rupture; athletes aged 15–21 showed significantly greater PTSD severity than those under 14. Conclusions: Rehabilitation of injured adolescent athletes must integrate structured psychological assessment alongside physical recovery. Acute post-injury mental health screening is essential. Evidence-based strategies — imagery training, goal setting, cognitive reframing, CBT, and psychologically informed practice — show promise but require further evaluation in paediatric populations.